The importance of organizational capacities for collaborative research: boundary crossings within a Swedish research–practice partnership - Maria Jarl; Mette Liljenberg; Klas Andersson; Magdalena Taube (Nordic Journal of Studies in Educational Policy, 2025)
Research – practice partnerships (RPPs) in education have been on the political agenda in Sweden during the last years. RPPs are long-term collaborations between higher education institutions and school districts (municipalities) and schools which intend to facilitate teacher-researcher collaboration in close relation to the teaching practice. This study focuses on a Swedish RPP between one university and multiple municipalities. It explores why two comparable municipalities differed in their success in the partnership’s core activity: calls for funding for collaborative research. Using the theoretical framework of absorptive capacity and boundary infrastructure, the internal organization of the two municipalities and how the RPP-initiative was docked into these organizations were analysed. We interviewed municipal- and school-level actors involved in the application processes within the two municipalities. Significant results include that for equal opportunities for teacher – researcher collaboration, municipalities must develop an organizational capacity that allows them to learn productively from external partners and recognize the knowledge provided by boundary spanners. This study contributes to the expanding literature on partners’ strategies to address emerging challenges of RPPs. It expands our understanding of how municipalities’ internal organization facilitates or hinders collaborative research within RPPs in education.